Patchouli Alcohol: A Natural Cardioprotectant Against Adriamycin-Induced Heart Failure - Shumin Lv; Hongwen Cai; Zhijun Wang; Jianhua Ye; Ligang Bao (Discovery Medicine, 2026)
Background: Patchouli alcohol (PA), a tricyclic sesquiterpene from Pogostemonis Herba, exhibits anti-inflammatory, antioxidant and cardiovascular activities. Adriamycin (Adr) induces dose-dependent cardiotoxicity that progresses to irreversible heart failure (HF). This study investigated the mechanism of PA in rats with Adr-induced HF. Methods: Male Sprague Dawley (SD) rats (initial n = 15/group) received intraperitoneal Adr (2 mg/kg, twice weekly for 4 weeks) to induce HF. Two weeks after modeling, PA (30 mg/kg/d) or Icilin (20 mg/kg/d) was administered for 4 weeks. Cardiac function (left ventricular ejection fraction (LVEF)/left ventricular short axis shortening rate (LVFS)), serum brain natriuretic peptide (BNP), lactate dehydrogenase (LDH), creatine kinase (CK), nitric oxide (NO), nitric oxide synthase (NOS), aspartate aminotransferase (AST), myocardial transient receptor potential melastatin 8 (TRPM8) and apoptosis-related proteins (Bcl-2 associated X protein (Bax), B-cell Lymphoma 2 (Bcl-2), and cleaved Caspase-3) were assessed. In vitro, Adr-treated AC16 cells were used to confirm the anti-apoptotic role of TRPM8 through PA treatment, N-(4-tert-butylphenyl)-N′-(3-chloro-4-fluorophenyl)urea (BCTC), and TRPM8 manipulation. Results: In vivo, PA and Icilin ameliorated cardiac dysfunction in Adr-induced HF rats (p < 0.05), downregulated HF markers and myocardial injury factors (p < 0.05), and mitigated Adr-induced myocardial pathological damage. Both agents also upregulated myocardial TRPM8 expression (p < 0.001) and reversed Adr-induced abnormal apoptosis-related proteins (p < 0.05), thus inhibiting excessive cardiomyocyte apoptosis. In vitro, PA suppressed Adr-induced AC16 cardiomyocyte apoptosis by upregulating TRPM8 (p < 0.01), whereas TRPM8 knockdown or inhibition abrogated PA's protective effect (p < 0.001). Conclusion: This study identifies PA as a novel pharmacological enhancer of TRPM8, demonstrating that PA exerts significant cardioprotective effects in Adr-induced HF by targeting TRPM8 and inhibiting cardiomyocyte apoptosis. These findings support TRPM8 as a key mediator of PA's protective role and provide a promising therapeutic strategy for HF management.